Colored Notation as a UDL (Universal Design for Learning) Strategy in Music Education: A Case Study - Silvana Nada Widyaswara; Sunarto Sunarto; Udi Utomo; Ritchie Manuel Pratama (Department of Special Education, 2025)
This study aims to examine the implementation of colored notation as a Universal Design for Learning (UDL) strategy in angklung music instruction at SLB Yapenas Yogyakarta, a school serving students with hearing impairments, intellectual disabilities, physical disabilities, and cerebral palsy. The research employed a qualitative approach using a case study design. Data were collected through participatory observations of angklung practice sessions, in-depth interviews with the music teacher and five students as key informants, and documentation analysis of instructional materials and recorded learning activities. The data were analyzed thematically to identify patterns aligned with the three core principles of UDL. The results indicate that colored notation effectively supports inclusive learning through: (1) Multiple Means of Representation, in which colors assist students in recognizing pitch, rhythmic patterns, and playing sequences while reducing cognitive load; (2) Multiple Means of Engagement, in which colors enhance students’ attention, motivation, and emotional comfort during music lessons; and (3) Multiple Means of Expression, in which students demonstrate increased confidence and accuracy in performing angklung pieces. These findings suggest that colored notation serves as a practical and replicable model for inclusive music education in other special schools